Fundamental Aspects of Education in the Light of the Spirituality of Unity [of the Focolare Movement] – Considering the Mystical Experience of Chiara Lubich - Scheidler, Monika (Paedagogia Christiana, 2019)
This contribution identifies and exemplifies the specific resources of inspiration and motivation that educators who live the spirituality of unity can exploit for their commitments in the field of education; that is, to create pedagogical relational spaces in particular.